2019
DOI: 10.1002/jbm.b.34524
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of mussel‐inspired nHA/OSA injectable hydrogel and repaired bone defect in rabbit

Abstract: With the rapid development of minimally invasive techniques in orthopedics, minimally invasive surgery combined with injection of bone repair materials has attracted increasing attention for the treatment of bone defects. Inspired by material in mussels, we decorated nanohydroxyapatite (nHA) with dopamine (DA) to form polydopamine (PDA)-decorated nHA (PHA). Then, we introduced PHA into a Schiff base reaction of oxidized sodium alginate (OSA) and gelatin (Gel) to prepare an injectable bone repair hydrogel under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Thus, mesoporous hydroxyapatites (mHA) scaffold retain the benefits of both hydroxyapatites and mesoporous structures. Experimental studies have shown that nanostructured hydroxyapatites were beneficial to the proliferation and osteogenic differentiation of hPDLCs (Ou et al, 2019), bone marrow mesenchymal stem cells (BMSCs) (Krishnamurithy et al, 2019;Liu et al, 2019;Jose et al, 2020) and adiposederived stem cells (ADSCs) (Huang et al, 2020). Moreover, nanostructured hydroxyapatites show higher levels of alkaline phosphatase activity than microhydroxyapatites (Domingos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mesoporous hydroxyapatites (mHA) scaffold retain the benefits of both hydroxyapatites and mesoporous structures. Experimental studies have shown that nanostructured hydroxyapatites were beneficial to the proliferation and osteogenic differentiation of hPDLCs (Ou et al, 2019), bone marrow mesenchymal stem cells (BMSCs) (Krishnamurithy et al, 2019;Liu et al, 2019;Jose et al, 2020) and adiposederived stem cells (ADSCs) (Huang et al, 2020). Moreover, nanostructured hydroxyapatites show higher levels of alkaline phosphatase activity than microhydroxyapatites (Domingos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] Therefore, it can be concluded that the compactness of the organic network structure might be affected by the content of modified Hap and crosslinking reagent in the hydrogel, which is well consistent with the previous report. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…In such cases other types of bone tissue substitutes are convenient to fill in the defect thanks to the plastic attributes of injectable scaffolds. The advantage of these injectable substitutes is the possibility of mini-invasive procedures (Liu et al 2019). A disadvantage of the pasty injectable substitutes is smaller mechanical support at the localisation of the bone defect.…”
Section: Discussionmentioning
confidence: 99%